2021
DOI: 10.1186/s12903-021-01685-y
|View full text |Cite
|
Sign up to set email alerts
|

The prescription pattern and awareness about antibiotic prophylaxis and resistance among a group of Egyptian pediatric and general dentists: a cross sectional study

Abstract: Background The use of antibiotics in dentistry as prophylaxis and treatment is frequent. Their misuse has led to a major public health problem globally known as antibiotic resistance. This study aimed to assess the pattern of antibiotic prescription and its prophylactic use for systemic conditions. Besides, this study evaluated the awareness and adherence to antibiotic prescription guidelines and antibiotic prophylaxis guidelines along with awareness of antibiotic resistance across pediatric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Those findings were further supported by another study conducted among general and paediatric dentists in North Carolina, USA that revealed low adherence to professional guidelines by dentists for prescribing antibiotics for dento-alveolar infections of children [63]. Moreover, similar to an array of other studies [59][60][61][62], the commonly prescribed antibiotics in our study were amoxicillin and metronidazole followed by amoxicillin with clavulanic acid. Therefore, routine patient statistics of this nature provides valuable insights in resource constrained settings at institutional sub-unit level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Those findings were further supported by another study conducted among general and paediatric dentists in North Carolina, USA that revealed low adherence to professional guidelines by dentists for prescribing antibiotics for dento-alveolar infections of children [63]. Moreover, similar to an array of other studies [59][60][61][62], the commonly prescribed antibiotics in our study were amoxicillin and metronidazole followed by amoxicillin with clavulanic acid. Therefore, routine patient statistics of this nature provides valuable insights in resource constrained settings at institutional sub-unit level.…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotics have revolutionized health care by preventing and controlling infections, however, since the era of penicillin the use of antibiotics has demonstrated a tremendous rise among medical and dental fraternities [59]. Accordingly, an overuse of antibiotics in dentistry in general and in paediatric dentistry [59][60][61][62] has been reported especially for the treatment of dento-alveolar infections among children [62]. Moreover, the same study revealed the majority of dentists especially those who had a high volume of child patients lacked adherence to professional guidelines for prescribing antibiotics for treatment of dental infections among children [62].…”
Section: Discussionmentioning
confidence: 99%
“…Ravichandran et al 17 , Kaul et al 18 and Suhaib et al 19 Agossa et al 20 26 documented that the most commonly prescribed antibiotic was Amoxicillin. However, according to Aly et al 27 Deniz-Sungur et al 28 Javed et al 29 and Shrestha et al 30 , the most often prescribed antibiotic was amoxicillin & clavulanic acid combination. Smith et al 31 found that amoxicillin was among the top antibiotics administered by dentists in England and Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, the use of systemic antibiotics has increased to a greater extent in dentistry, and it is still common in day-to-day practice. In the healthcare sector, 3% to 11% of total antibiotic prescriptions are from dentistry [6][7][8] to prevent infections. Dental infections are composed of different types of bacteria, such as gram-positive, gram-negative, and anaerobes [9].…”
Section: Introductionmentioning
confidence: 99%